Effects of WhatsApp as Vocabulary Instructional Tool for Distance Learning among Tertiary Students - Kasturi, Sivabalan; Zuraina, Ali (JOCSSES, 2022)
The reality of Malaysia is no longer the same after COVID-19. Most of the sectors were affected due to pandemic and that includes the education field. Therefore, the Malaysian government had imposed the Movement Control Order (MCO) to curb the pandemic, which eventually disrupts teaching and learning process.